Exploring the nexus between financial inclusion, governance, and carbon emissions in SAARC countries - Jafir Mehmood; Yang Jinghan; Jing Wang; Maqsood Ahmad (Heliyon)
This study examines the impact of financial inclusion (FI) and institutional quality (INSQ) on carbon dioxide (CO2) emissions in South Asian Association for Regional Cooperation (SAARC) economies, using data from 2004 to 2022. The hypotheses were tested using a generalized method of moments (GMM) approach. Beside, a robust moment method quantile regression (MM-QR) static model and Granger causality tests were employed to validate the results. The findings indicate that FI indicators, such as bank branches of commercial banks (BOCB) and automated teller machines (ATMs) are positively associated with CO2 emissions. Similarly, the INSQ has a significant positive impact on CO2 emissions. Control variables, including foreign direct investment (FDI), financial development (FD), and population growth (PG), are also positively linked to CO2 emissions, whereas globalization (GI) has a negative impact. Robustness tests confirm that the effects of FI and INSQ on CO2 emissions vary across economic contexts, with unidirectional causality observed between BOCB and CO2 and bidirectional causality between ATMs and CO2. This study highlights the need for policymakers in SAARC countries to balance their economic development and environmental sustainability. Integrating environmentally friendly technologies and practices into financial and institutional development strategies is essential. Promoting green banking, strengthening environmental regulations, and leveraging globalization for cleaner technologies can help mitigate the adverse effects of FI and INSQ on CO2 emissions. This study underscores the importance of incorporating environmental considerations into economic and financial policies to achieve sustainable development.